Corticomedullary mixed tumour resembling a small adrenal gland-involvement of cancer stem cells: case report - Duan, Lian; Tang, Zili (BMC endocrine disorders, 2017)
Background: Adrenal corticomedullary mixed tumours are very rare. Its mechanism is rarely reported. Here we report the first case of a corticomedullary mixed tumour resembling a “small adrenal gland” with distinct arrangement of the cortical and medullary layers. We further hypothesize regarding the tumorigenic mechanism of this tumour.